Pendidikan Siyasah Syari’iyah Dalam Perspektif Islam - Maizal Efendi; M. Rafi Dhaifullah; Badri Badri; Wismanto Wismanto; Nursyafna Nursyafna; Rifka Andriani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The scope of Islamic teachings is very broad and universal. It is hoped that Islam will not only be a means of ritual activities, but Islam will also be able to respond to this and become an absolute foundation for social life. One dimension of Islam is the country's government system. Islam also offers a concept and system of government that is based on noble religious values. The state is a vehicle for maintaining and enforcing Islamic law for the wider community. Objective To achieve this, Islamic law must be implemented formally in state institutions, as was done by the Prophet Muhammad SAW and continued by the state under the khulafaurrasyid of Medina. This research uses a qualitative method based on a research library. Searching for discussion material through books, magazines and journal articles is the most dominant study. The data found is then codified and then put into descriptive writing. The results of this research show that sharia education from an Islamic perspective is indeed very important, as long as Muslims are lazy to enter the world of state politics, the nation they live in will actually be controlled by infidels.